(untitled) (The Research of Medical Science Review, 2025)
INTRODUCTION: It is acknowledged that type 2 diabetes is a major public health issue that significantly affects both human life expectancy and medical costs. Diabetes alone is among the top ten cause of death, accounting for almost 1 million fatalities annually. The most common cause of mortality for diabetic individuals is diabetic nephropathy which is also the primary cause of kidney failure. Ethnicity, family history, gestational diabetes, high blood pressure, dyslipidaemia, obesity, and insulin resistance are the main risk factors for diabetic nephropathy, according to several epidemiological studies. OBJECTIVE: To determine the frequency of diabetic nephropathy in type 2 diabetic patients presented to Mardan Medical complex. STUDY DESIGN: Cross Sectional. STUDY SETTING: Department of General Medicine, MMC, Mardan. STUDY DURATION: 17-04-2024 to 17-10-2024. SUBJECTS AND METHODS: For 165 patients, urine samples were ‎taken and were sent to laboratory to determine the presence or absence of albumin through urine R/E. Blood samples from all patients were taken to determine serum creatinine level in order to estimate Glomerular Filtration Rate (GFR) using Cockcroft-Gault formula. Diabetic Nephropathy as per operational ‎definition was recorded on specially designed proforma. RESULTS: Mean and standard deviation calculated for age was 48.21 ± 11.20 years, for BMI was 27.05 ± 3.45 kg/m², and for diabetes duration was 11.06 ± 6.61 years. Majority patients (30.3%) were in the 30-40 years group. Gender distribution showed 63% male and 37% female. The study found that 69.1% were literate, 66.1% lived in urban areas, and 81.8% were married. Diabetic nephropathy (DN) was observed in 33.3% of the participants. CONCLUSION: Given that diabetic nephropathy ‎is a leading cause of end-stage renal disease globally, understanding its prevalence and the factors contributing to its development is crucial for effective disease management. The findings of this study indicate a significant 33.3% prevalence with male predominance of 20.6% within the study population, which aligns with previous studies. Additionally, this study suggests further investigation into the environmental, genetic, and lifestyle factors contributing to the disparities in DN rates globally.